2022
DOI: 10.1155/2022/1119931
|View full text |Cite
|
Sign up to set email alerts
|

An Analytical Study for Assessing Water Productivity in Pre‐ and Post‐Rehabilitation Period of Rural Tank System

Abstract: Water productivity is the ratio of the amount of water applied to the field in cubic meter and the net return gained in rupees. Increased water productivity leads to an improved occupational value for the farmers. Tank rehabilitation allows for additional water to be added to an irrigation tank, increasing water production. Hence, this study is carried out to assess the net return for a unit of water used in the pre- and post-rehabilitated period of rural tank “Pelasur” in Thiruvannamalai district of Tamil Nad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 59 publications
(56 reference statements)
0
1
0
Order By: Relevance
“…They found that rehabilitation resulted in higher annual incomes, with a benefit-cost ratio exceeding 1.5. Anuradha et al [44] found that rehabilitating the Pelasur tank in Thiruvannamalai district, Tamil Nadu, significantly improved water productivity. Deivalatha et al (2014) [45] found that desilting tank beds and supply channels in Ponpadi, Tamil Nadu, increased crop productivity from 4800 to 5400 in the first season and 4425 to 5400 in the second.…”
Section: Discussionmentioning
confidence: 99%
“…They found that rehabilitation resulted in higher annual incomes, with a benefit-cost ratio exceeding 1.5. Anuradha et al [44] found that rehabilitating the Pelasur tank in Thiruvannamalai district, Tamil Nadu, significantly improved water productivity. Deivalatha et al (2014) [45] found that desilting tank beds and supply channels in Ponpadi, Tamil Nadu, increased crop productivity from 4800 to 5400 in the first season and 4425 to 5400 in the second.…”
Section: Discussionmentioning
confidence: 99%
“…Food security requires a consistent supply of water, especially in areas with high population density. This can be achieved by capturing rainwater to combine surface and groundwater [24,25]. Rainwater harvesting not only stabilizes agricultural output but also enhances productivity and aids in restoring degraded lands.…”
Section: Introductionmentioning
confidence: 99%